Aplikasi Lombok Tourism Berbasis Android - Adi Setiawan; Justinus Andjarwirawan (Jurnal Infra, 2017)
Lombok is a beautiful and interesting place to visit, but due to lack of local interest and attention, now Lombok becomes less advanced, but when compared to other places in Indonesia, Lombok so is beautiful. This app will help tourists who want to travel on the island of Lombok, and also very much information can diperoleh of the features of this application, such as when wistawan want to see the beautiful scenery but do not know the road to get there, it will be guided by the route features in this app , and also when it runs out of money, gasoline and others, there is a nearby feature that can show the user the nearest position now and which should go. Users can plan a trip with because it has a feature where users can plan their trips themselves. Having a nearby feature where the ad shows seeking atm / rental car and gas station nearby which can make the user become quiet and a lot of information about the surrounding area. Users can find the desired location with ease for their routes in the specified so that it can follow the route that and get to the goal